2012
DOI: 10.1016/j.jcps.2012.09.002
|View full text |Cite
|
Sign up to set email alerts
|

Giving from a distance: Putting the charitable organization at the center of the donation appeal

Abstract: Past research has shown repeatedly that people prefer donating to a single identified human victim rather than to unidentified or abstract donation targets. In the current research we show results countering the identifiable victim effect, wherein people prefer to donate to charitable organizations rather than to an identifiable victim. In a series of five studies, we manipulate temporal and social distance, examine a variety of donation targets, and measure intention to donate time or money as well as actual … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
78
0
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 133 publications
(89 citation statements)
references
References 62 publications
3
78
0
4
Order By: Relevance
“…Rather than measuring donation magnitude, we adhered to the stream of academic research examining intentions, which has been extended specifically to charitable giving(Ein-Gar and Levontin, 2013;White and Peloza, 2009;Xie and Bagozzi, 2014). Extant research also indicates that participants may be unable to remember exact donation amounts and that such measures lend themselves to increased social desirability bias(Mathur, 1996).Encouraging Consumer Charitable Behavior: The Impact of Charitable Motivations, Gratitude,……”
mentioning
confidence: 99%
“…Rather than measuring donation magnitude, we adhered to the stream of academic research examining intentions, which has been extended specifically to charitable giving(Ein-Gar and Levontin, 2013;White and Peloza, 2009;Xie and Bagozzi, 2014). Extant research also indicates that participants may be unable to remember exact donation amounts and that such measures lend themselves to increased social desirability bias(Mathur, 1996).Encouraging Consumer Charitable Behavior: The Impact of Charitable Motivations, Gratitude,……”
mentioning
confidence: 99%
“…As most donations are made to assist individuals who are not personally known by the donor, issues such as beneficiary similarity and proximity can instead be considered when deciding who should be offered assistance (Small, 2011). In situations where greater distance is observed, individuals tend to engage in more abstract thinking (referred to as lowlevel construal, Alter & Oppenheimer, 2008), which in turn can negatively impact upon their willingness to help (Ein-Gar & Levontin, 2013).…”
Section: What Motivates People To Donate To Charity?mentioning
confidence: 99%
“…Temporal distance refers to whether the need is immediate or future-focused in nature -for example it has been found that donating blood is more viewed as a future-oriented activity (Ein-Gar & Levontin, 2013). Social distance refers to the level of similarity between oneself and the individual being observed (Trope, Liberman, & Wakslak, 2007), which may include national group membership (Kogut & Ritov, 2005).…”
Section: What Motivates People To Donate To Charity?mentioning
confidence: 99%
“…Researchers term this phenomenon the 'identifiable victim effect' (Small & Loewestein 2003;Ein-Gar & Levontin 2013) and have attempted to reveal its causes. The 'proportion of the reference group effect' is one of the factors that explains why consumers are more generous to identifiable victims: consumers are more sensitive to proportions than to absolute numbers when they evaluate life and objects with non-transparent values (Baron 1997;Small et al 2007) because proportions are easier to interpret (Slovic et al 2002).…”
Section: How To Show? Statistical Vs Identifiable Victimsmentioning
confidence: 99%